2008
DOI: 10.1590/s0102-86502008000200002
|View full text |Cite
|
Sign up to set email alerts
|

Burn wound angiogenesis is increased by exogenously administered recombinant leptin in rats

Abstract: Background: Leptin is a potent direct angiogenic factor that stimulates endothelial cell migration and activation in vitro and angiogenesis in vivo. In addition, leptin has been discussed to play an important role in angiogenesis, as it promotes the formation of new blood vessels. Purpose: The effect of exogenously administered leptin on the healing process of a full tissue burn wound model. Methods: Sixty-three Sprague-Dawley male rats were used. Full tissue burn wound was created by electrocautery. The width… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 32 publications
1
17
0
2
Order By: Relevance
“…In the present study, reduced adipokine levels were observed in the presence of injury rather than disuse, suggesting a greater influence of the injury component. Administration of leptin in burned rats has been shown to increase angiogenesis in injured tissues and decrease multiple organ damage [54,55]. Resistin was not altered in the present studies, but has been reported to be decreased in children with burns [56].…”
Section: Discussionmentioning
confidence: 42%
“…In the present study, reduced adipokine levels were observed in the presence of injury rather than disuse, suggesting a greater influence of the injury component. Administration of leptin in burned rats has been shown to increase angiogenesis in injured tissues and decrease multiple organ damage [54,55]. Resistin was not altered in the present studies, but has been reported to be decreased in children with burns [56].…”
Section: Discussionmentioning
confidence: 42%
“…We also observed that ANGPT1 showed the statistically significant decrease in mRNA expression 1 day after the skin incisions. These factors have been reported to promote angiogenesis [6,[19][20][21]23,27,33,34], and their decreases may indicate that complex mechanisms may be involved in our skin wound system.…”
Section: Discussionmentioning
confidence: 99%
“…(CSF3/G-CSF) [11][12][13][14][15], chemokine (C-X-C motif) ligand2 (CXCL2) [16,17], chemokine (C-X-C motif) ligand 12 (CXCL12/SDF1) [18][19][20][21], endothelin 1 (ET1) [22], fibroblast growth factor 1 (FGF 1) [23], hepatocyte growth factor (HGF) [24,25], hypoxia inducible factor 1 alpha (HIF1a) [26], leptin [27], matrix metallopeptidase 9 (MMP9) [18,28,29], serpine/plasminogen activator inhibitor 1 (PAI1) [29][30][31], platelet-derived growth factor-A (PDGF-A) [18,32], transforming growth factor alpha (TGFa) [33,34], transforming growth factor beta 1 (TGFb1) [35,36], tenomodulin (TNMD) [37], and troponin I type 2 (TNNI2) [38,39]. Factors known to be involved in lymphangiogenesis such as fibroblast growth factor 2 (FGF 2) [40,41], c-fos induced growth factor (FIGF/VEGF-D) [42,43], forkhead box C 2 (FOXC2) [44][45][46], and prospero homeobox 1 (PROX1) [46][47][48][49] are also included in the study.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of these studies have focused on a single adipokine at a time in patients. Recently, in animal models of burns, significant alterations in adipokines have been reported, and interventions to attenuate these responses have been associated with improved outcomes [8-10]. Increasing evidence of alterations in adipokines in critically ill patients and promising interventional studies in animals have led to a rethinking of the role of adipose tissue in the care and outcome of the critically injured patient, with the possibility of novel therapeutic interventions.…”
Section: Introductionmentioning
confidence: 99%